Asian Traditions of Meditation - Eifring, Halvor 1960- (University of Hawaii Press, 2016)
Meditation has flourished in different parts of the world ever since the foundations of the great civilizations were laid. It played a vital role in the formation of Asian cultures that trace much of their heritage to ancient India and China. This volume brings together for the first time studies of the major traditions of Asian meditation as well as material on scientific approaches to meditation. It delves deeply into the individual traditions while viewing each of them from a global perspective, examining both historical and generic connections between meditative practices from numerous historical periods and different parts of the Eurasian continent.